Good Practice Report : Postgraduate Research and Coursework Degrees. - Hamilton, Jillian; Thomas, Mandy; Carson, Susan; Ellison, Elizabeth (Office for Learning and Teaching, 2014)
A coherent, high quality good practice report will be produced to synthesise information and resources developed by national learning and teaching projects and Fellowships on postgraduate coursework and research degrees. A textual analysis of project reports will provide an overview and project summaries, identify and classify key themes, and collate project outcomes into a summative report. A literature review of scholarly publications on postgraduate degrees will provide a complementary resource. Gaps identified in project reports will be crosschecked against subsequent projects and the literature review, and any areas warranting further investigation will be identified and summary recommendations made. The resources, models, scholarly publications and exemplars of good practices produced by national projects and fellowships will be listed and cross-referenced. The resulting summative good practice report and its collation of scholarly outcomes and resources will increase access to the tools that academics and their universities can employ to improve the delivery and development of postgraduate programs.